Miracle Question Technique to Reduce Academic Procrastination in Junior High School Students - Dias Nur Oktavianti Hasanah; Dewi Masyitoh; Ika Romika Mawaddati (TAUJIHAT: Jurnal Bimbingan Konseling Islam, 2024)
This study aims to examine the effectiveness of the miracle question technique in reducing academic procrastination among seventh-grade students at SMP IT Grafika Pesanggaran. The researcher used a quantitative experimental approach with a Single Subject Research model A-B design. The researcher selected subjects through purposive sampling, selecting students with the highest procrastination scores as determined by the questionnaire. In phase A (baseline), the researcher measured the initial conditions of procrastination behaviour. Furthermore, in phase B (intervention), the researcher provided individual counselling services using the miracle question technique. This technique is designed to help students imagine ideal future conditions, explore optimistic hopes, self-potential, and desired solutions to their problems, thereby encouraging more positive behavioural changes. The research instrument used was the Academic Procrastination Scale, which was adapted from the original model by Ferrari, Johnson, and McCown (1995). The researcher used descriptive analysis to compare academic procrastination score data from phase A (baseline) to phase B (intervention) using Microsoft Excel. The descriptive analysis showed a gradual decrease in procrastination scores from 106 (very high) to 55 (low). Thus, the miracle question technique has proven effective as a counselling strategy for helping students overcome academic procrastination.